A Dynamic Topology Reformation Algorithm for Power Saving in ZigBee Sensor Networks. (13th November 2013) - Wang, Reen-Cheng; Chang, Ruay-Shiung; Yen, Jei-Hsiang; Lee, Pu-I
Abstract : ZigBee is a protocol suite based upon IEEE standard 802.15.4 for the construction of low-rate wireless personal area networks. Since most of ZigBee devices are powered by battery, the power saving is an important issue. In the past several years, many solutions are proposed to extend battery life by reducing device transmitting and receiving time. However, few studies have noticed that most energy is consumed in sensing and monitoring rather than communicating activities, since the data rates in most ZigBee networks are low. Besides, energy will consume the most of those nodes which act as routers or are orphans that cannot join the network. In order to extend the life time of network, we proposed a dynamic topology reformation algorithm. The algorithm consists of a cluster reformation scheme for enhancing connectivity and a self-swapping method for averaging the loading of router nodes and end devices. As the experimental result shows, compared with the ZigBee standard, our method gains 6.02% to 15.13% improvement in network join ratio. And the role swapping balances the power consumption which makes the lifetime of the whole network 1.3 to 1.375 times longer.